دور الاتصالات التسویقیة المتكاملة في تحسین الصورة الذهنیة باستخدام نموذج التحلیل العاملي التوكیدي - دراسة میدانیة لسوق الألبسة - مراكشي , عبد الحمید (Finance and Business Economies Review, 2018)
This paper focuses on the impact of integrated marketing communication on improving brand image by studying an analytical statistic that requires prior research to determine the marketing communication mix used in this market by examining for distributors, wholesalers and retailers before measuring the impact using the empirical analysis model. After the matching of the proposed model and a different calculation as the indicators of absolute conformity, comparative conformity, and economic matching, which were confirmed, the values were extracted, which was positive and statistically significant. The combination of marketing communication has an effect on improving the mental image through its three dimensions.